Analysis of the Penta Helix Model in Halal Tourism Development in Trowulan, Mojokerto Regency - Lucky Abdul Herdiyanto; Maryam Bte Badrul Munir (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to describe the role of Penta Helix Model actors on the development of Halal Tourism in Trowulan, Mojokerto Regency and to describe the supporting and inhibiting factors of the role of penta helix model actors on the development of halal tourism in Trowulan, Mojokerto Regency. The results of this study are five actors in the form of government, business, community, academics, and media that play a role in the development of halal tourism in Trowulan. The conclusion of this research is that the penta helix actors are not running optimally because there is no binding regulation for the five roles to collaborate with each other and there is no legal umbrella for the development of halal tourism. The research suggestion is that the government forms a team consisting of the roles of the penta helix and makes a legal umbrella for reference to the development of halal tourism in Trowulan, Mojokerto district.